Stomach contents and seasonal variation of diet composition of cobia, Rachycentron canadum in the Dungun Coast Malaysia - Babatunde, T. A.; Amin, S. M. N.; Md Yusoff, F.; Arshad, A. (Triveni Enterprises, 2020)
Aim: Analysis of food and feeding habit of cobia, R. canadum in Dungun coat, Malaysia was carried out in this research in order to provide information on their diet preference and feeding intensity of cobia in the area.